2008
DOI: 10.1245/s10434-008-9969-z
|View full text |Cite
|
Sign up to set email alerts
|

Which Is the Optimal Risk Stratification System for Surgically Treated Localized Primary GIST? Comparison of Three Contemporary Prognostic Criteria in 171 Tumors and a Proposal for a Modified Armed Forces Institute of Pathology Risk Criteria

Abstract: The NIH, modified NIH, and AFIP criteria are useful in the prognostication of GIST, and the AFIP risk criteria provided the best prognostication among the three systems for primary localized GIST. However, remarkable prognostic heterogeneity exists in the AFIP high-risk category, and with our proposed modification, this system provides the most accurate prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 25 publications
7
76
0
Order By: Relevance
“…Nonetheless, neoplasms with muscle differentiation showed greater disease-free intervals 17 . However, the authors point out that these results need to be evaluated carefully, since the tumors with muscle differentiation had a less aggressive biological course.Regarding the two GIST prognostic characterization systems, there was evidence of association with prognosis in both Fletcher et al 7 and Miettinen et al 11 classification, which was also found by other authors 14,18,24,25 .However, in this series we found a better risk statistical correlation with the Miettinen et al 11 classification. This can be explained by the introduction of a third criterion (location), the study of more than 2,000 cases, with long follow-up of patients and mainly the greater stratification of the risk categories, allowing a reclassification of the neoplasias 25 .…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Nonetheless, neoplasms with muscle differentiation showed greater disease-free intervals 17 . However, the authors point out that these results need to be evaluated carefully, since the tumors with muscle differentiation had a less aggressive biological course.Regarding the two GIST prognostic characterization systems, there was evidence of association with prognosis in both Fletcher et al 7 and Miettinen et al 11 classification, which was also found by other authors 14,18,24,25 .However, in this series we found a better risk statistical correlation with the Miettinen et al 11 classification. This can be explained by the introduction of a third criterion (location), the study of more than 2,000 cases, with long follow-up of patients and mainly the greater stratification of the risk categories, allowing a reclassification of the neoplasias 25 .…”
supporting
confidence: 86%
“…Regarding the two GIST prognostic characterization systems, there was evidence of association with prognosis in both Fletcher et al 7 and Miettinen et al 11 classification, which was also found by other authors 14,18,24,25 .…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The dramatic effect of imatinib has led to an increased awareness of these tumours and this coupled with developments in diagnosis including detection of CD117 and CD34 may have led to higher incidence rates comparative to the pre-imatinib era. Goettsch et al described an incidence rate of 2.1/million in 1995 and 12.7/million in 2003 [18]. The Norweigan study demonstrated a rate increase from 1.8 per million per million to 12.5 per million comparing 1980-1984 data to 2000-2004 [8].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have investigated the main resultant predictors (9,(13)(14)(15). Some factors are widely recognized as being predictive of recurrence, and several risk stratification scales have been proposed (2,(16)(17)(18)(19)(20). Despite these risk assessments, approximately 10% of GISTs have an unexpected course, suggesting that many other factors affect their behavior.…”
Section: Original Articlementioning
confidence: 99%